Genetic analysis of Bacterial Blight (Xanthomonas Oryzae pv. Oryzae Ishiyama) Resistance and Yield in Rice (Oryza sativa L.) - Devika R (Department of Plant Breeding and Genetics, College of Agriculture, 2002)
Bacterial blight disease caused by Xanthomonas oryzae pv. oryzae Ishiyama is a major constraint limiting rice production in Kerala especially in Kuttanad, the rice bowl of Kerala. Keeping in view the limited success achieved in controlling the disease with conventional chemicals, the present investigation entitled "Genetic analysis of bacterial blight (Xanthomonas oryzae pv. oryzae Ishiyama) resistance and yield in rice (Oryza sativa L.)" was carried out at Rice Research Station, Moncompu for the genetic analysis of bacterial blight resistance and yield in rice for developing high yielding disease resistant varieties through the estimation of genetic variability in a collection of germplasm, screening and identification of resistant donors, estimation of combining ability and gene action by line x tester analysis and the estimation of the gene action involved in the inheritance of bacterial blight resistance and yield by generation mean analysis. One hundred and fifty genotypes collected from various sources VIZ., International Rice Research Institute, Philippines, Directorate of Rice Research, Hyderabad, different Rice Research Stations of Kerala Agricultural University and local varieties of rice cultivated in Kuttanad, Palakkad and Wyanad were evaluated in the field adopting a randomised block design with two replications at Rice Research Station, Moncompu